Changes of Ammonia-Metabolizing Enzyme Activity and Gene Expression of Two Strains in Shrimp Litopenaeus vannamei Under Ammonia Stress - Qiu, Liguo; Shi, Xiang; Yu, Simeng; Han, Qian; Diao, Xiaoping; Zhou, Hailong (Frontiers in Physiology, 2018)
Ammonia stress can inhibit the survival and growth, and even cause mortality of shrimp. In this study, ammonia-metabolizing enzyme activities and gene expression were compared between two strains of L. vannamei under different ammonia-N (NH4+) concentrations (3.4, 13.8 and 24.6 mg/L). The results showed that elevated ammonia concentrations mainly increased glutamine synthetase (GSase) activities while inhibiting transglutaminase (TGase) activities in the muscle of both strains. Thus, we concluded that L. vannamei could accelerate the synthesis of glutamine from glutamate and NH4+ to alleviate ammonia stress. Compared with the muscle, the hepatopancreas plays a major role in ammonia stress and might be a target tissue to respond to the ammonia stress. Compared to the control group, the treatment of high ammonia concentrations reduced the hepatopancreas TGase gene expression and increased the gene expression rates of glutamate dehydrogenase-β (GDH-β) and GSase in both the muscle and the hepatopancreas of the two strains (p < 0.05). The genes (GDH-β and GS) in strain B were not only expressed earlier but also at levels higher than the expression range of strain A. At the gene level, strain B showed a more rapid and positive response than strain A. These data might help reveal the physiological responses mechanisms of shrimp adapt to ammonia stress and speed up the selective breeding process in L. vannamei.